Clicking as perceiving: an analysis of the usability of multimedia applications - Gomes, Cristina Caramelo (2012)
O presente artigo examina algumas condicionantes da comunicação digital na actualidade dentro do âmbito do nível de percepção e interpretação. Deste modo, recorre às conclusões de estudos semióticos de Yuri Lotman e segue a definição de usabilidade como avaliação heurística de Jakob Nielsen. A metodologia utilizada inclui uma análise de websites oficiais da New York Academy of Arts e da Yale University School of Art, centrando-se em fatores que produzem impacto na sua usabilidade e interpretação. As conclusões apontam para o facto de o processo cognitivo ser decisivo na definição da sua usabilidade. This paper discusses the constraints of present-day digital communication, linking it to the degree of perception and interpretation. Therefore, it uses the contributions of semioticians Yuri Lotman and Peirce and follows Jakob Nielsen’s definition of usability as heuristic evaluation. Methodology includes an analysis of the official websites of the New York Academy of Arts and the Yale University School of Art, focusing on factors that produce impact on their usability and interpretation. Conclusions show that the cognitive process is decisive to define usability.